The Evaluation Of Primary Canal Discharge In Pulo Ie Thoe Irrigation Area, Nisam District, North Aceh Regency - Zakiatil Khairah; Wesli (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
This study aims to determine the amount of discharge taken and discharged available in the Pulo Ie Thoe Irrigation AreaNisam District, North Aceh Regency. This Irrigation Area has an area of 40 ha. The Pulo Ie Thoe irrigation area requires the largest average withdrawal discharge of 0.0947 m3/s in July so that 0.0947 m3/s is available to meet agricultural needs.The irrigation area of Pulo Ie Thoe has an available discharge of 92.56 m3/s for a 2-year renewal period. The Pulo Ie Thoe Irrigation Area has enough water to meet irrigation activities in the area. So that there is a water balance, which is a condition where the amount of water available is more than the amount of water needed. The existing channel design resulted in a channel discharge of 0.051816 m3/s. The discharge of the channel has a smaller value compared to the discharge needed in the Irrigation Area so that the irrigation channel is not able to drain the discharge for the irrigation area so it needs to be redesigned. The design of the planned channel is 0.85 m wide, 0.45 m in flow, with a wet cross-sectional area of 0.383 m2, and a wet circumference of 1.76 m. The design of this planned channel produces a discharge of 0.10323 m3/s so that it is able to drain the required discharge in the Pulo Ie Thoe Irrigation Area.